Understanding the implementation of the holiday activities and food programme in the North East of England using normalization process theory - Defeyter, Margaret Anne; Finch, Tracy; Crilley, Eilish Samantha; Shinwell, Jackie; Mann, Emily (Frontiers in Public Health, 2022)
Following several pilot projects, in 2020, the Department for Education (DfE) in England committed funding of £220M p. a to its Holiday Activities and Food (HAF) programme to support all 153 upper-tier local authorities, comprising City Councils, County Councils and Metropolitan Borough Councils, to provide an activity and food programme for children who are in receipt of means-tested free school meals. In this study, qualitative interviews were conducted with representatives from three Local Authorities in the North East of England who were responsible for overseeing the implementation and delivery of HAF programmes in their Local Authority area to examine how the summer HAF programme was implemented during summer 2021. Interviews were conducted with eight participants prior to the implementation of the HAF programme, and four interviews were conducted after the programme had been delivered. Using a directed content analysis approach, an interpretative framework was co-developed, based on the four constructs (and selected sub-constructs) of Normalization Process Theory. This framework guided data coding. The analysis aimed to identify and understand the barriers and opportunities in relation to HAF implementation within local authorities. Participants did not perceive HAF as a totally new initiative as many had either commissioned or delivered holiday clubs in the past. However, the increased scale and scope of HAF was perceived as highly complex, involving multiple local authority departments and stakeholders. Nonetheless, HAF funding enabled local authorities to improve the quality and reach of their holiday programmes. Strong networks and good communication between all stakeholders supported successful delivery, despite tight delivery timescales. However, the rigidity of some of the DfE guidance was a barrier for some providers, particularly the recommended delivery model of 4 h a day, 4 days a week for 4 weeks, with many individual holiday clubs struggling to meet this level of delivery, and local authority leads interpreting the guidance at a club level rather than an individual child access level. Furthermore, participants considered the HAF eligibility criteria too restrictive. Many councils were developing long-term plans for HAF delivery, integrated into planning across several departments, and all local authorities were actively seeking ways to engage with and embed HAF within local communities.